Study of Cancer Immunotherapy Mechanisms in Pancreatic Adenocarcinoma and Pheochromocytoma Murine Models - Uher, Ondřej (Jihočeská univerzita, 2022)
This dissertation examines the study of intratumoral cancer immunotherapy using a combination of phagocytosis-stimulating ligands and Toll-like receptor ligands (TLR) in murine pancreatic adenocarcinoma and pheochromocytoma murine models. In this study, we show that intratumoral application of the phagocytosis-stimulating ligand Mannan-BAM and three TLR ligands, referred to as MBT therapy, efficiently suppresses tumor growth in more than 83% of mice bearing murine melanoma. However, in aggressive pancreatic adenocarcinoma and pheochromocytoma murine models, such a combination is inefficient and must be combined with an agonistic anti-CD40 antibody, referred to as MBTA therapy, to achieve complete eradication of the tumor. We show that complex intratumoral MBTA therapy can systemically increase the recruitment of innate immune cells followed by activation of adaptive immune cells not only in treated tumors but also in distal non-treated lesions, resulting in the reduction of tumor growth and prolonged survival of treated mice. Taken together, these findings highlight the effect of MBTA therapy and the potential to optimize this therapeutic approach for future use in clinical trials as a treatment for metastatic cancers.
Study of Cancer Immunotherapy Mechanisms in Pancreatic Adenocarcinoma and Pheochromocytoma Murine Models
Keywords: intratumoral; immunotherapy; cancer; pancreatic adenocarcinoma; pheochromocytoma; intratumoral; immunotherapy; cancer; pancreatic adenocarcinoma; pheochromocytoma